Efficacy and Safety of Antivascular Endothelial Growth Factor (Anti-VEGF) in Treating Neovascular Age-Related Macular Degeneration (AMD): A Systematic Review and Meta-analysis - Xiaobei Yin; Ting He; Shanshan Yang; Hui Cui; Wenlan Jiang (Journal of Immunology Research)
This study is aimed at assessing the efficacy and safety of antivascular endothelial growth factor (anti-VEGF) inhibitors in treating age-related macular degeneration (AMD). PubMed, Embase, and Cochrane library were searched. Weighted mean difference (WMD) and relative risk (RR) with 95% confidence interval (CI) were applied to assess outcomes. Eighteen randomized controlled trials involved 8,847 neovascular AMD patients were selected for the meta-analysis. Pegaptanib (WMD: 6.70; P<0.001) and ranibizumab (WMD: 17.80; P<0.001) were associated with greater BCVA changes than control after 1 year. Bevacizumab was linked with less changes in central macular thickness after 1 year compared to control (WMD: -38.50; P<0.001), but more changes compared to ranibizumab (WMD: 10.69; P=0.024). The incidence of gain of 15 or more letter visual acuity after 1 year was increased when compared with bevacizumab versus control (RR: 7.80; P=0.001), pegaptanib versus control (RR: 2.83; P=0.015), and ranibizumab versus control (RR: 3.92; P=0.003). Moreover, ranibizumab was associated with more BCVA changes and an increased incidence of gain of 15 or more letter visual acuity after 2 years compared with control (RR: 5.77; P<0.001). This study found that most anti-VEGF inhibitors provided better efficacy than non-anti-VEGF intervention, and the treatment effectiveness among various anti-VEGF agents was equally effective.